2007
DOI: 10.1016/j.ultsonch.2006.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound-assisted extraction of anthocyanins in red raspberries and identification of anthocyanins in extract using high-performance liquid chromatography–mass spectrometry

Abstract: Anthocyanins (Acys) are naturally occurring compounds that impart color to fruit, vegetables and plants. The extraction of Acys from red raspberry (Rubus idaeus L. var. Heritage) by ultrasound-assisted process (UAP) was studied. A central composite rotate design (CCRD) was used to obtain the optimal conditions of ultrasound-assisted extraction (UAE), and the effects of operating conditions, such as the ratio of solvents to materials, ultrasonic power and extraction time, on the extraction yield of Acys were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(120 citation statements)
references
References 29 publications
4
112
1
3
Order By: Relevance
“…The increase of blueberry pomace content in cookie formulation led to decrease in b * values, indicating the presence of characteristic blue anthocyanins such as 3-glycosidic derivatives of delphinidin, malvidin and petunidin (Routray and Orsat 2011). Addition of raspberry pomace in formulation increased the redness of cookies, due to the presence of characteristic red pigment cyaniding-3-sophoroside (Chen et al 2007). Changes in the cookies color reflected the composition of present anthocyanins in the pomace.…”
Section: Color Of the Cookiesmentioning
confidence: 99%
“…The increase of blueberry pomace content in cookie formulation led to decrease in b * values, indicating the presence of characteristic blue anthocyanins such as 3-glycosidic derivatives of delphinidin, malvidin and petunidin (Routray and Orsat 2011). Addition of raspberry pomace in formulation increased the redness of cookies, due to the presence of characteristic red pigment cyaniding-3-sophoroside (Chen et al 2007). Changes in the cookies color reflected the composition of present anthocyanins in the pomace.…”
Section: Color Of the Cookiesmentioning
confidence: 99%
“…Figure 1a showed that the yield of polysaccharides was influenced by the ultrasonic power greatly and increased with the increase of ultrasonic power till 150 W. And when the power was over 150 W, the yield decreased. It is well known that the ultrasonic could destroy cell walls of plants, and the yield of anthocyanin from fresh fruits was enhanced by the increasing power in the early period (Chen et al 2007). However, the extracted polysaccharides may be degraded with the higher ultrasonic power and the yield of polysaccharides decreased (Hromádková et al 2002).…”
Section: Effects Of Extraction Power On Polysaccharides Yieldmentioning
confidence: 99%
“…Ultrasound-assisted extraction (UAE) has been widely used for the extraction of nutritional material, such as lipids (Metherelet al, 2009), proteins (Zhu et al, 2009), flavoring (Chen et al, 2007;Da Porto et al, 2009), essential oils (Kimbaris et al, 2006) and bioactive compounds (e.g., flavonoids (Ma et al, 2008), carotenoids (Sun et al, 2006;Yue et al, 2006) and polysaccharides (Iida et al, 2008;Chen et al, 2010;Wei et al, 2010;Yan et al, 2011). Compared with traditional solvent extraction methods, ultrasound extraction can improve extraction efficiency and extraction rate, reduce extraction temperature, and increase the selection ranges of the solvents (Vilkhu et al, 2008).…”
Section: Ultrasound Extractionmentioning
confidence: 99%